PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI MAN 2 PADANGSIDIMPUAN - Rawalan Harapan (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2016)
The aim of this study was to find out is there any significant effect of headmaster’s leadership to teacher’s activity at MAN 2 Padangsidimpuan through quantitative method. The population used in this study was less than 100 people and the data was analyzed by using statistic while the instrument in collecting data used Likert scale. Based on test of hypothesis, there was no significant effect of headmaster’s leadership to the teacher’s activity in MAN 2 Padangsidimpuan, it showed from α = 0,05 dan n = 67 formulates into dk = n-2 = 67-2 =65 and the result is 2,72 3,99. Actually the teacher’s activity has influenced of other factors besides of headmaster’s leadership.